The origins and development of early Mycenaean culture - Dickinson, O; Dickinson, O. T. P. K. (1970)
﻿ In the Introduction, the development of theories about the prehistoric cultures of the Aegean, particularly the Mycenaean culture of the Greek mainland, is sketched. It is argued that the greatest deficiencies of all theories are that they have failed to take enough account of the culture preceding the Mycenaean, the Middle Helladic, and have too readily assumed that the mainland was a cultural unity in the Middle and Late Bronze Age. The intention of this thesis is to consider the remains from a chronological and regional point of view, in which the Middle Helladic culture, the Shaft Graves, and the evidence for Early Mycenaean development outside the Argolid will all be given separate treatment. The term 'Early Mycenaean' is defined as being the period from the adoption of Mycenaean culture to the horizon of destructions marked by Late Minoan IB pottery, equivalent to the pottery-phases Late Helladic I and IIA; the following period, to the fall of Knossos, is called 'Middle Mycenaean'. [continued in text ...]